Strategi Calvin dalam Perkembangan Pendidikan Agama Kristen Era Reformasi dan Relevansinya Pada Masa Kini (International Forum of Researchers and Lecturers, 2023)
Calvin's strategy in the development of Christian religious education in the Reformation era was key in forming a strong and sustainable approach to Christian religious education. John Calvin, a leading figure of the Christian Reformation in the 16th century, had a central role in advancing Christian religious education. He implemented a number of important strategies, including education for all, structured education, teaching of Scripture, training of church leaders, character education, involvement of church and state, and emphasis on local languages. These strategies help spread Calvinist theology and ensure everyone's access to quality Christian religious education. Calvin's influence on Christian education is still visible in various Christian education systems to this day. Christian religious education is education in Christian teachings that emphasizes aspects of knowledge, attitudes and values ​​and even skills that are based on the Christian faith itself. With Calvin's strategy in the midst of Christian Religious Education, Christian Religious Education can achieve the goals it should achieve, especially in the community, schools and families. In this series of strategies, Calvin played a key role in changing Christian religious education in his time. Christian religious education is no longer the exclusive right of clergy, but is a right and responsibility for the entire Christian community. Calvin's in-depth and structured educational approach, along with his emphasis on the use of print media, helped spread the teachings of the Protestant Reformation throughout the Christian world. These approaches remain influential in the development of Christian religious education to this day.